2013
DOI: 10.5348/ijhpd-2013-12-cs-3
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticoduodenectomy after Roux-en-Y gastric bypass: A single institution retrospective case series

Abstract: Introduction:The unique challenges of pancreaticoduodenectomy in a patient with altered midgut anatomy secondary to RouxenY gastric bypass are seldom discussed in surgical literature. We discuss two such cases at our institution, in light of experiences of other authors. Case Series: The two cases reported here are different from the majority of previously reported cases as remnant gastrectomy was not performed in either patient. However, one patient did receive a gastrostomy tube in the gastric remnant. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In the included articles, 25 patient cases were reported; our institution included an additional case, for a total of 26 cases (Fig. 1 ) [ 13 20 ]. Table 1 contains a synopsis of all reported cases with regard to clinicopathological characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the included articles, 25 patient cases were reported; our institution included an additional case, for a total of 26 cases (Fig. 1 ) [ 13 20 ]. Table 1 contains a synopsis of all reported cases with regard to clinicopathological characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Procedures included pancreaticoduodenectomy [ 21 ], pylorus-preserving pancreaticoduodenectomy [ 1 ], and total pancreatectomy [ 1 ]. Report of resection margin status [ 13 ] and histologic lymph node examination [ 4 ] for malignancies were infrequently provided. The gastric remnant was resected in majority of patients [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Articles cited within the initially identified batch were also screened and a total of seven cases and series were identified for inclusion. [5][6][7][8][9][10][11]…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature review A literature search revealed seven publications describing a total of 14 patients. [5][6][7][8][9][10][11] The preoperative workup, operative management of the remnant stomach and reconstruction, and postoperative complications are summarized in Table 4. The indications for surgery were variable and included both benign and malignant processes.…”
Section: Hpbmentioning
confidence: 99%
See 1 more Smart Citation